2005
DOI: 10.1007/s00415-005-0989-3
|View full text |Cite
|
Sign up to set email alerts
|

Markers of lacunar stroke in patients with moderate internal carotid artery stenosis

Abstract: The benefits of surgical correction of moderate internal carotid artery stenosis have been demonstrated only in symptomatic subjects. It is debatable whether patients with lacunar infarct ipsilateral to a moderate carotid stenosis may be considered symptomatic like those with large-artery stroke. The aim of the study was to seek markers capable of differentiating patients with lacunar or non-lacunar stroke ipsilateral to a moderate internal carotid artery stenosis. We enrolled 95 patients with a first stroke i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…18 Similarly, lacunar strokes were included as endpoint as they had been associated with a poor hemodynamic response in patients with carotid stenosis. 11 Another point to discuss is the relatively high incidence of stroke in our cohort compared with more recent studies. 31,32 One explanation is that our study population might have been at particularly high risk, as we included subjects with a mean age above 70 years undergoing ultrasonographic evaluation of neck vessels for the presence of multiple vascular risk factors.…”
Section: Discussionmentioning
confidence: 76%
“…18 Similarly, lacunar strokes were included as endpoint as they had been associated with a poor hemodynamic response in patients with carotid stenosis. 11 Another point to discuss is the relatively high incidence of stroke in our cohort compared with more recent studies. 31,32 One explanation is that our study population might have been at particularly high risk, as we included subjects with a mean age above 70 years undergoing ultrasonographic evaluation of neck vessels for the presence of multiple vascular risk factors.…”
Section: Discussionmentioning
confidence: 76%
“…Of these, about 10–15 % patients fulfil criteria for behavioural variant frontotemporal dementia (bvFTD) [ 13 , 28 ]. In keeping with the pattern of cognitive change, frontal lobe abnormalities have been demonstrated in MND both on structural [ 2 , 17 ] and functional [ 1 , 18 ] imaging. bvFTD may precede, follow or coincide with the onset of motor symptoms [ 24 ], reinforcing the inter-relationship between the two disorders.…”
Section: Introductionmentioning
confidence: 86%
“…Patients with arterial stenosis >50% ipsilateral to an SDI are often classified as having a nonlacunar infarction. 29,30 However, whether the arterial disease is the actual cause of the SDI or a coincidental disease occurring in a patient with symptomatic small vessel disease remains unclear. 31 Symptomatic carotid stenosis derives greater benefit from vascular intervention compared to asymptomatic carotid stenosis.…”
Section: Arterial Small Deep Infarctsmentioning
confidence: 99%
“…32,33 Other studies also suggest that arterial disease is the cause of some SDIs, with the degree of vascular stenosis, intima medial thickness, and arterial stiffness all having been reported as predictors of nonlacunar stroke. 7,18,29,30,[34][35][36][37][38][39][40][41][42] Additionally, Tejada et al reported a 7% absolute increase in ipsilateral compared to contralateral carotid stenosis in patients with SDIs, suggesting that carotid disease contributes to some SDIs. 43 However, this finding has not been demonstrated by others.…”
Section: Arterial Small Deep Infarctsmentioning
confidence: 99%